Accelerated Plethysmography in Glaucoma Patients - Hinako Takei; Yuto Yoshida; Misaki Ukisu; Keigo Takagi; Masaki Tanito (Biomedicines, 2025)
Background: Systemic arterial stiffness and atherosclerosis have been increasingly recognized as potential contributors to the pathogenesis of glaucoma. Several studies have reported associations between glaucoma and various surrogate markers of vascular stiffness. However, despite the growing interest in the vascular components of glaucoma, no previous studies have specifically explored the relationship between the indices derived from acceleration plethysmography (APG) and glaucoma. This study seeks to address this gap by investigating the potential association between APG parameters and the presence of glaucoma. Methods: The subjects were 701 patients (mean age 68.6 years, 54% male) with open-angle glaucoma (primary open-angle glaucoma [POAG] or exfoliation glaucoma [EXG]), and 94 control subjects (mean age 60.1 years, 57% male) who had no eye diseases other than cataracts. The subjects were all cases in which APG was measured using a sphygmograph (TAS9 Pulse Analyzer Plus View; YKC Corp., Tokyo, Japan). The amplitude of waveform types (a, b, c, d, and e-waves) and derived vascular types (A, B, and C) of the accelerated pulse wave components were statistically compared between the cases and controls. Results: The accelerated pulse wave components (mean ± standard deviation) of the control and glaucoma groups were a-wave 785 ± 99 and 776 ± 93 (p = 0.40), b-wave −522 ± 161 and −491 ± 143 (p = 0.050), c-wave −142 ± 108 and −156 ± 105 (p = 0.24), d-wave −288 ± 144 and −322 ± 122 (p = 0.014), and e-wave 103 ± 79 and 90 ± 58 (p = 0.059), with differences between the groups being observed in the b and d-waves. For derived vascular types, compared with the controls and POAG, patients with EXG had a lower frequency of Type A and a higher frequency of Type C than the other groups (p = 0.044). Multivariate analysis showed that factors significantly associated with vascular type included age (p < 0.0001), sex (p < 0.0001), diastolic blood pressure (p = 0.021), and pulse rate (p < 0.0001), while BMI, systolic blood pressure, history of hypertension, history of diabetes, presence or absence of glaucoma, and presence or absence of pseudoexfoliation material were not significant. Conclusions: This is the first study to investigate the relationship between APG and glaucoma with a large sample size. In elderly glaucoma patients, particularly those with EXG, systemic vascular changes are often present. APG parameters may reflect vascular alterations in glaucoma.